New approaches to disease, disability and medicine in Medieval Europe - Connelly, Erin; Künzel, Stefanie (Archaeopress Publishing Ltd, 2018)
An interdisciplinary collection of papers focusing on infections, chronic illness, and the impact of infectious diseases on Medieval society, with contributions by academics from a variety of disciplines and a diverse range of international institutions.